Optimal Fleet Size, Delivery Routes, and Workforce Assignments for the Vehicle Routing Problem with Manual Materials Handling - Boonprasurt, Prachya; Nanthavanij, Suebsak (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
<span style="font-family: ";Times New Roman";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Angsana New'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;">The vehicle routing problem with manual materials handling (VRPMMH) is introduced. At customer locations, delivery workers must manually unload goods from the vehicle and take them to the stockroom. The delivery activities require workers to expend certain amounts of physical energy. In this paper, two models of VRPMMH are developed, namely VRPMMH models with fixed workforce assignments (FXW) and with <span style="font-family: ";Times New Roman";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Angsana New'; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: TH;" lang="EN-CA">flexible workforce assignments (FLW)<span style="font-family: ";Times New Roman";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Angsana New'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;">. The objective of both VRPMMH models is to determine optimal fleet size and delivery routes such that the total cost is minimized. Additionally, the second model is intended to assign delivery workers to vehicles to minimize the differences in physical workload.